Quantifying Potential Error in Painting Breast Excision Specimens. (23rd May 2013) - Fysh, Thomas; Boddy, Alex; Godden, Amy
Abstract : Aim. When excision margins are close or involved following breast conserving surgery, many surgeons will attempt to reexcise the corresponding cavity margin. Margins are ascribed to breast specimens such that six faces are identifiable to the pathologist, a process that may be prone to error at several stages. Methods. An experimental model was designed according to stated criteria in order to answer the research question. Computer software was used to measure the surface areas of experimental surfaces to compare human-painted surfaces with experimental controls. Results. The variability of the hand-painted surfaces was considerable. Thirty percent of hand-painted surfaces were 20% larger or smaller than controls. The mean area of the last surface painted was significantly larger than controls (mean 58996 pixels versus 50096 pixels, CI 1477–16324, P = 0.014 ). By chance, each of the six volunteers chose to paint the deep surface last. Conclusion . This study is the first to attempt to quantify the extent of human error in marking imaginary boundaries on a breast excision model and suggests that humans do not make these judgements well, raising questions about the safety of targeting single margins at reexcision.